Neural correlate of Internet use in patients undergoing psychological treatment for Internet addiction. (4th May 2017) - Lai, Carlo; Altavilla, Daniela; Mazza, Marianna; Scappaticci, Silvia; Tambelli, Renata; Aceto, Paola; Luciani, Massimiliano; Corvino, Stefano; Martinelli, David; Alimonti, Flaminia; Tonioni, Federico
Abstract: Background : The new version of Diagnostic and Statistical Manual of Mental Disorders (DSM-5th) proposed the Internet Gaming Disorder for the diagnosis of Internet addiction (IA) considering the neurobiological evidence of the craving. Aims : The aim was to test the neural correlate in response to the Internet cue in patients with IA. Methods : Sixteen males with IA diagnosis (clinical group) and 14 healthy male (control group) were recruited for an experimental visual task composed of Internet images and emotional images. During the visual presentation of Internet cue, electroencefalographic data were recorded using Net Station 4.5.1 with a 256-channels HydroCel Geodesic Sensor Net. Event-related potential (ERP) components and low-resolution electromagnetic tomography (sLoreta) were analysed. Results : sLoreta analyses showed that patients from the clinical group presented a higher primary somatosensorial cortex and lower paralimbic, temporal and orbito-frontal activation in response to both Internet and emotional images compared to those of the control group. Conclusions : These results suggest that clinically recognized pathological use of Internet could be linked to dissociative symptoms.